HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) DENGAN DISMENOREA PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Pande, Ni Nyoman Utami Wijayaswari; Purnawati, Susy (E-Jurnal Medika Udayana, 2016)
CORRELATION OF BODY MASS INDEX (BMI) AND DYSMENORRHEA AMONG MEDICAL STUDENTS OF UDAYANA UNIVERSITY ABSTRACT Dysmenorrhea is the most common gynecologic complaints for adolescents and women by the age of young adult. Prevalence of dysmenorrhea is high. This complaint affects quality of women’s life during reproductive time. The objective of this research is to know correlation of body mass index (BMI) and dysmenorrhea among college students of medical faculty Udayana University. The research using cross sectional design conducted on 279 respondents. All respondents were given a questionnaire to complete, questions were related to menstruation and menstrual pain. BMI was calculated from weight and height. After been gained of respondents who experienced dysmenorrhea then categorised according to pain degrees of dysmenorrhea. Chi-square was used to analyze the correlation between dysmenorrhea and pain degrees of dysmenorrhea with BMI. The mean age of respondents at menarche was 12.5 years and the prevalence of dysmenorrhea was high (74.9%). The majority of experienced dysmenorrhea having BMI within the normal range. Respondents who experienced mild pain is the highest of mostly on BMI category underweight and overweight. The results obtained in this study shows that there was no relationship between dysmenorrhea and BMI and there was no relationship between pain degrees of dysmenorrhea and BMI category underweight and overweight.
Keywords: Dysmenorrhea, BMI, pain degrees of dysmenorrhea